Opportunities to Use Virtual Laboratories to Facilitate Biology Learning in High Schools - Sari, Nella Puspita; Yusuf, Munawir; Yamtinah, Sri (Universitas Sebelas Maret, 2023)
Technological developments have changed the way students learn, many students prefer to use smartphones to study compared to using books. Learn-ing biology itself is learning that requires students to do a lot of activities so the right method used is a problem-based and experimental learning method. However, schools cannot provide all learning facilities such as practicum equipment. Therefore, teachers can use existing technology such as digital learning media to support learning. This type of research is qualitative de-scriptive research. The focus of the research is 32 student’s science majors of grade 2 high school students. Methods of data collection using interviews and using a questionnaire. The analysis was carried out in four stages: data collection, data reduction, data preconcludinging conclusions. The results of the study show that there is a great opportunity for conducting experiment-based learning with the help of a smartphone, such as using a virtual labora-tory. As many as 81% of students said that practicum would help them un-derstand biology concepts. Additionally, 94% of students use technology to help them learn. Thus using of virtual laboratories is an opportunity to over-come the lack of learning facilities and can encourage students to be more active in learning activities.